Impulsivity and novel object recognition test of rat model for vascular cognitive impairment after antipsychotics treatment - Ronny T Wirasto; Irwan Supriyanto; Arif Prassetyo; Nunu N Madjid; Susini R Sari; Baiq R Rhadianaa; Heru Yulianto; Nur Arfian; Nyoman Kertia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTVascular cognitive impairment (VCI) is a common condition in which no standard treatment has been approved. VCI is often accompanied by behavioral problems which require psychiatric interventions. The common therapeutic agent used for the acute management is antipsychotic injections. Current findings showed that atypical antipsychotic possess better safety profile for treating behavioral problems related to VCI compared to typical antipsychotic. In this study, we induced VCI in Sprague Dawley rats between 6-8 weeks old using bilateral carotid communist artery occlusion technique. The subjects were divided into 4 treatment groups: sham, olanzapine, haloperidol, and risperidone groups. Subjects received intramuscular injections of subsequent drugs for 3 days post VCI induction. Impulsive behavior and object recognition were examined using cliff jumping test and novel object recognition test. The analyses results showed that impulsive behavior was lower in the olanzapine and haloperidol groups compared to sham group, although it was not statistically significant (p = 0.651). The results also showed that there were no significant differences in the time spent exploring old and novel objects in all groups (p = 0.945;0.637 respectively). In conclusion, antipsychotic injection might not be effective to control impulsive behavior post VCI induction.